Developing a Strategic Model of Child-Friendly Pesantren Climate to Prevent Sexual Violence - Kholik, Abdul; Fauziah, R. Siti Pupu; Ramdhani, Muhammad Rendi; Suharsiwi, Suharsiwi (Jurnal Ilmiah Peuradeun, 2025)
Sexual violence in pesantren remains a pressing concern despite the implementation of national child protection policies. This study developed a strategic model of a child-friendly pesantren climate to prevent sexual violence by integrating institutional, cultural, and relational dimensions. Using a qualitative multiple-case study design, data were collected from 15 pesantren in West Java, Jakarta, and Banten through in-depth interviews, focus group discussions, and non-participatory observations to ensure credibility and depth. Data analysis followed Miles and Huberman’s interactive model—comprising data reduction, display, and conclusion drawing—supported by NVivo 12 for thematic coding. The findings revealed that preventing sexual violence cannot rely solely on written policies and staff training. It also required cultural mediation that translates formal rules into daily practices and an alliance between staff and families that reconceptualizes institutional capacity as a shared relational commitment. These mechanisms, together with institutional child protection policies, inclusive pedagogy, physical and psychological safety, student agency, and parental involvement, formed a comprehensive model for cultivating a child-friendly pesantren climate. This model advanced theoretical discourse by reframing the hidden curriculum as a vehicle for safeguarding and by positioning family involvement as integral to institutional competence, while offering a practical roadmap for policymakers and practitioners to strengthen child protection in Islamic boarding schools.